Comparison of burden among family members of patients diagnosed with schizophrenia and bipolar disorder in a large acute psychiatric hospital in China. Issue 1 (December 2016) - Zhou, Yanling; Rosenheck, Robert; Mohamed, Somaia; Ou, Yufen; Ning, Yuping; He, Hongbo
Abstract Background The difference of burden between caregivers of acute patients with schizophrenia and bipolar disorder has not been well studied in China, a culture where family responsibility has a very high value. Our aim is to compare family burden in these two categories diagnosis and to identify predictors of family burden in a large psychiatric hospital in China. Methods Two hundred forty-three schizophrenic patients and 200 bipolar patients were enrolled in a cross-sectional study. Patients were independently evaluated on symptoms, insight, attitudes toward medication, quality of life during the first week of their admissions. The prime caregiver for each patient was also evaluated with a standard measure of family burden within 1 week of patients' admission. Results Caregiver perceptions of violent behavior and suicidal risk among patients with bipolar disorder were significantly greater than among families of those with schizophrenia. Hierarchical regression analyses demonstrated differential correlates of burden for all predictive factors with R2 values ranging from 0.14 to 0.27 in the five burden factors in schizophrenia families; and from 0.12 to 0.24 in bipolar disorder families. Symptoms severity explained the greatest proportion of variance, whereas patient and caregiver demographic variables explained much less variance. Conclusion Family burden, especially the caregiver perceptions of violent and suicidal behaviors were greater in care givers of acute bipolar disorder patients than among caregivers of schizophrenia patients in the present sample. However, in families of patients with both disorders clinical features were the strongest predictor of caregiver burden.